The Politics of Market Linkage: Linking Domestic Climate Policies with International Political Economy - Jessica F. Green; Thomas Sterner; Gernot Wagner (Fondazione Eni Enrico Mattei (FEEM), 2014)
After twenty years of global negotiations, the world is still far from a comprehensive climate agreement. The 'top-down' approach embodied by the Kyoto Protocol has all but stalled, chiefly due to disagreements over levels of ambition and objections to financial transfers. To avoid those problems, many have shifted their focus on bottom-up 'linkage' of regional, national, and sub-national cap-and-trade systems. Decentralized architecture has its appeals, but we argue that linkage among carbon markets ultimately faces the same obstacles that are at the heart of global climate negotiations. Linkage can potentially reduce overall costs of tackling climate change by leveraging the differences in the marginal costs of emissions reductions across nations. However, as incomes, ideologies and other conditions diverge - and, thus, potential economic gains from linkage increase - political obstacles to linkage grow. We identify four obstacles to successful linkage: potential for gaming of targets; objections to financial transfers; the difficulty of close regulatory coordination; and incompatibility with other domestic policy objectives. Linkage, thus, may be an important political instrument and learning process but it provides no end run around international "global warming gridlock" (Victor 2011). A functioning global climate policy architecture still requires close international coordination with a balance of 'bottom-up' and 'top-down' elements. Only with this realization - and by employing a gradual process toward full linkage - can early carbon market linkages help facilitate a path towards a successful global climate architecture.
Keywords: Q5; Q54; Q58; 330; Climate Change; Global Warming; Cap and Trade; Carbon Tax; Linkage; Climate Finance; Political Economy; Kyoto; Copenhagen; Paris